Toxicologycal and physiological activity of plant extracts against Spodoptera littoralis (Boisduval)(lepidoptera: Noctuidae) larvae - Hatem, A.E.=700 1 Abdel-Samad, S.S.M.; Saleh, H.A.; Sliman, M.H.A.; Huáien, A.I.
(Es, En)
Ilus., 56 ref.
Keywords: BRAáICA NIGRA; RAPHANUS SATIVUS; SPODOPTERA LITTORALIS; LARVAS; PLAGAS DE PLANTAS; CONTROL BIOLOGICO; SONCHUS; TOXICIDAD; INSECTICIDAS DE ORIGEN VEGETAL; ESPAÑA; BOLETIN DE SANIDAD VEGETAL: PLAGAS